The Farewell to a Monarch, the Monument to a Monarch. Jan Matejko (1838–1893) - Kłak-Ambrożkiewicz, Marta (Requiem, 2025)
The article focuses on presenting the funeral ceremonies of the master painter Jan Matejko and outlines the origins of the establishment of the first biographical museum on Polish soil the Jan Matejko House Museum (currently a branch of the National Museum in Kraków). The museum was founded in 1895, largely thanks to the financial support of Poles from all three partitions. It was established and still operates today in Jan Matejko’s townhouse on Floriańska Street.